Study on Mencius’ theory of human nature and moral concepts - Deng, Jiafu (2024)
The concept of morality is an essential aspect of moral education and cultivation, which has been the focus of attention for philosophers throughout history. As the culmination of Confucian thought, Mencius contributed significantly to the moral concepts that form an integral part of Confucianism and traditional Chinese culture. This article focuses on Mencius’ moral philosophy, explicitly examining his theory of human nature and the concept of an ideal personality. By exploring these ideas, the paper aims to elucidate the contemporary relevance of Mencius’ moral philosophy.